Rough Sets and Current Trends in Computing 8th International Conference, RSCTC 2012, Chengdu, China, August 17-20, 2012.Proceedings - Yao, JingTao; Yang, Yan; Slowiński, Roman; Greco, Salvatore; Li, Huaxiong; Mitra, Sushmita; Polkowski, Lech (Lecture Notes in Artificial Intelligence,, 2012)
This book constitutes the refereed proceedings of the 8th International Conference on Rough Sets and Current Trends in Computing, RSCTC, held in Chengdu, China, in August 2012, as one of the co-located conferences of the 2012 Joint Rough Set Symposium, JRS 2012. The 55 revised full papers presented together with one keynote paper were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on rough sets and its applications; current trends in computing; decision-theoretic rough set model and applications; formal concept analysis and granular computing; mining complex data with granular computing; data mining competition.